Pengembangan E-modul Berbasis Problem Based Learning untuk Memfasilitasi Higher Order Thinking Skills (HOTS) Siswa - Usi, Usiminda; Oktaviana, Dwi; Irvandi, Wandra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to develop an e-module based on problem based learning to facilitate students' higher order thinking skills (HOTS) with the material taken being trigonometric comparisons. The research design used in this study was the ADDIE development model (analysis, design, development, implementation, evaluation). The subjects in this study were the development subjects and the product trial subjects. The development subjects were validators and the product trial subjects were students of class X Phase E1 of SMA Negeri 1 Belitang. The results of this study were: (1) the developed e-module obtained very valid criteria with media validity reaching 92% and material validity reaching 93%, (2) the e-module met practical criteria based on the results of student and teacher response questionnaires with practicality reaching 89.5%, (3) the effectiveness of the e-module was seen based on the results of the student posttest with an index percentage of 73.1% with effective criteria.